Establishing motion control in children with autism and intellectual disability: Applications for anatomical and functional MRI. Issue 1 (14th October 2016) - Cox, Alison D.; Virues‐Ortega, Javier; Julio, Flavia; Martin, Toby L.
Abstract : Excessive motion makes magnetic resonance imaging (MRI) extremely challenging among children with autism spectrum disorder (ASD). The medical risks of sedation establish the need for behavioral interventions to promote motion control among children with ASD undergoing MRI scans. We present a series of experiments aimed at establishing both tolerance of the MRI environment and a level of motion control that would be compatible with a successful MRI. During Study 1, we evaluated the effects of prompting and contingent reinforcement on compliance with a sequence of successive approximations to an MRI using a mock MRI. During Study 2, we used prompting and progressive differential reinforcement of other behaviors (DRO) to promote motion control in a mock MRI for increasing periods of time. Finally, during Study 3, some of the participants underwent a real MRI scan while a detailed in‐session motion analysis informed the quality of the images captured.